EXISTÊNCIA E RELIGIÃO EM ALBERT CAMUS: Relações entre o absurdo e a revolta - Almeida, Kleiton Cerqueira de (2010)
The present research pursuits from two fundamental bases of Albert Camus thought, which are, absurd and the revolt discusses the relation between Camus thought and religion with regard to his refusal to accept the conception or attitude that resorts to a meaning beyond human existence. Camus - who was an Algerian writer and received a Nobel Prize for Literature in 1959. He conceived the absurd as an experience resultant of the awareness of asymmetry current in the human existence. This asymmetry is set in the extreme between the human desire for happiness, unity and fullness and the evidence expressed by pain, fragmentation and limitation. The revolt exists in this scenery as Camus answer for the simultaneously demand for justice and revolt against death. As far as religion is concerned, Camus understands it as an escape founded on hope. This escape neglects and impedes the extreme consideration of human condition. The religious hope, in short, invalidate the revolt as a legitimate answer to the existential condition, as it intends to justify the injustice as an answer to a mystery. As it was provided the description of absurd and the revolt, this research turns to Paul Tillich s thought, a German theologian and philosopher, as a theoretical reference in order to analyse the specific relation between religion and Camus thought. The concept of religion and faith in Paul Tillich is as an important element as it takes into consideration the existence of an ambiguity in the religious experience, performed by Paul Tillich from the dialogue between finite and infinite, or, in other words, between the being and the no being. From Paul Tillich, we ask about the possibility of religion, even amid statement of the impossibility of the eternal. So, there ensue to the consideration that the carrying out of religious experience in Camus as an expression of a profane transcendence, where the refusal of God take communion with an everlasting demanding for perfection and eternity.